"Biopellet" as One of Future Promising Biomassbased Renewable Energy: a Review - Wahyono Yoyon (EDP Sciences, 2021)
The depletion of fossil energy reserves and not environmentally friendly fossil energy emissions makes it necessary to use renewable energy as an alternative to replacing fossil energy. Biopellet is one of the renewable energy based on biomass that exists in Indonesia. Biopellets are produced from a base of abundant biomass. Thus, biopellets have the potential and promise to continue to be used as fuel by humans. The literature review includes the characteristics of biopellets and the application of biopellets as fuel. Biopellets can be made by mixing biomass with an adhesive with a concentration of 15% (w/w) then stirred until homogeneous and put into a pellet mill for printing. The pellets were dried in an oven for 30 minutes. Biopellet characteristically has complied with SNI 8021-2014 for parameters of ash content, fixed carbon content, caloric value, water content, and volatile matter content. The application of biopellet as a stove material also shows good performance for heat, efficiency, and emission parameters. In conclusion, biopellet is a renewable energy fuel based on biomass that has potential in the present and promising in the future.